Anti-Inflammatory Effects of Anthocyanin-Enriched Black Soybean Seed Coat (BSSC) Crude Extract on LPS-Induced Acute Liver Injury in Mice - Yu-Tang Tung; Chun-Liang Tung; Cheng-Chia Hsieh; Yu-Chen Huang; Shiming Li; Chun-Liang Tung; Jyh-Horng Wu (MDPI AG, 2024)
Soybeans rank among the top five globally produced crops. Black soybeans contain anthocyanins in their seed coat, offering strong antioxidant and anti-inflammatory benefits. This study explores the protective effects of black soybean seed coat (BSSC) against acute liver injury (ALI) in mice. Mice pretreated with BSSC crude extract showed reduced liver damage, inflammation, and apoptosis. High doses (300 mg/kg) of the extract decreased levels of proinflammatory cytokines (IL-6, IFN-γ) and increased levels of anti-inflammatory ones (IL-4, IL-10), alongside mitigating liver pathological damage. Additionally, it influenced the Nrf2/HO-1 pathway and reduced levels of apoptosis-related proteins. In vitro, the compounds delphinidin-3-O-glucoside (D3G) and cyanidin-3-O-glucoside (C3G) in BSSC were found to modulate cytokine levels, suggesting their role in ALI protection. The study concludes that BSSC extract, particularly due to D3G and C3G, effectively protects against LPS-induced ALI in mice by inhibiting inflammation, oxidative stress, and apoptosis.